THE EFFECTIVENESS OF THE USE OF FLOATING EXCAVATORS IN INCREASING STUDENTS KNOWLEDGE OF TIDAL FLOODING FOR FARMERS IN THE COASTAL AREAS OF JAVA - Qristin Violinda; Aan Burhanuddin; Achmad Buchori; Sumarno Sumarno; Nur Cholifah (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2022)
Indonesia is a country with a very high level of vulnerability to disasters. Disasters that have often occurred in Indonesia have caused significant loss of life and material. Students as agents of change need to have good knowledge of disaster preparedness in order to provide positive changes to the community regarding disaster preparedness. The purpose of this study was to analyze the level of knowledge of PGRI Semarang University students regarding disaster preparedness through the effective use of floating excavators. The method used in this research is descriptive analytic. The sample in this study were PGRI University students who met the inclusion criteria set by the researcher. Sampling using purposive sampling technique. Data analysis was carried out using univariate analysis which was carried out on the characteristics of the respondents, namely age and gender and categorical variables, namely knowledge using percentage and proportion sizes. The results showed that as many as 207 (65.1%) respondents had an increased and good level of knowledge regarding disaster preparedness through the effective use of floating excavators. The conclusions obtained from the results of this study are that the students of PGRI Semarang University already have a good level of knowledge which may be caused by disaster preparedness training through the effective use of floating excavators. Therefore, the floating excavator is one of the tools that can be used in disaster management that students can learn.